Deviating Gender Roles of the Main Characters in Enola Holmes Movie - Tenteyali, Ester; Baga, Magdalena; Usu, Novi Rusnarty (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research examines gender roles representation in the 2020 film Enola Holmes by analyzing the characterization of the main characters, Enola Holmes and Viscount Tewksbury. Using Stuart Hall’s (1997) theory of representation, this research explores how the film constructs, negotiates, or challenges traditional Victorian-era gender norms. The study employs a qualitative descriptive method supported by intrinsic and extrinsic approaches. The findings show that Enola is portrayed as an independent, intelligent, and courageous young woman who challenges the expectations placed on women in the Victorian era. Meanwhile, Tewksbury is depicted with a gentler and more expressive form of masculinity, which contrasts with dominant male stereotypes of the period. These representations indicate that the film introduces and constructs more flexible interpretations of gender identities and highlights the shifting meaning of gender roles through film. Accordingly, the main characters deviate from the gender role meaning in that era.